Substantial understory contribution to the C sink of a European temperate mountain forest landscape - Dirnböck, T. (Landsc Ecol, 2020)
CONTEXT: The contribution of forest understory to the temperate forest carbon sink is not well known, increasing the uncertainty in C cycling feedbacks on global climate as estimated by Earth System Models. OBJECTIVES: We aimed at quantifying the effect of woody and non-woody understory vegetation on net ecosystem production (NEP) for a forested area of 158 km(2) in the European Alps. METHODS: We simulated C dynamics for the period 2000–2014, characterized by above-average temperatures, windstorms and a subsequent bark beetle outbreak for the area, using the regional ecosystem model LandscapeDNDC. RESULTS: In the entire study area, woody and non-woody understory vegetation caused between 16 and 37% higher regional NEP as compared to a bare soil scenario over the 15-year period. The mean annual contribution of the understory to NEP was in the same order of magnitude as the average annual European (EU-25) forest C sink. After wind and bark beetle disturbances, the understory effect was more pronounced, leading to an increase in NEP between 35 and 67% compared to simulations not taking into account these components. CONCLUSIONS: Our findings strongly support the importance of processes related to the understory in the context of the climate change mitigation potential of temperate forest ecosystems. The expected increases in stand replacing disturbances due to climate change call for a better representation of understory vegetation dynamics and its effect on the ecosystem C balance in regional assessments and Earth System Models. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10980-019-00960-2) contains supplementary material, which is available to authorized users.